Species of Euglossa (Glossura) and E. (Glossuropoda) (Hymenoptera: Apidae: Euglossina) occurring in the Amazon, including new records for Brazil - Nemésio, André; Ferrari, Rafael R. (Zootaxa, 2011)
Species of Glossura Cockerell, 1917 (genus Euglossa Latreille, 1802) are among the most common orchid-bees in inventories carried out in the Brazilian Amazon. Nevertheless, recent re-definitions of the subgenus, as well as recently described species, made recognition of individual species more difficult. In this study we review all species belonging to the subgenus occurring in the Amazon Basin, as well as those species belonging to the closely related subgenus Glossuropoda Moure, 1989, and report new records of Euglossa (Glossura) lugubris Roubik, 2004 and Euglossa (Glossura) occidentalis Roubik, 2004 for Brazil. Additionally, an illustrated identification key for all fifteen species of both subgenera recorded for the Amazon Basin is provided.